Secondary school learners' perceptions of the value of integrating ICT into the curriculum: an exploratory study in the Grahamstown circuit - Mbane, Nombeko Precious (Rhodes University, Faculty of Education, Department of Education, 2009)
According to the Draft White Paper on e-Education (DoE, 2003), the objective of ICTs in education is to build digital and information literacy so that all learners become confident and competent in using technology to contribute to an innovative and developing South African society. International researchers have acknowledged that little is known about learners' perceptions of their own learning, but that learners are aware of how technology can be used and have the potential to contribute ideas about ICTs can be used to support their learning. To add to this growing body of research, this study sought to establish secondary school learners' experiences and perceptions of the value of integrating ICT into the curriculum and the extent to which they believe that ICT is meaningfully integrated into the curriculum. Although some of the schools do not have the necessary ICT infrastructure, this did not preclude the learners from having opinions about the potential benefits and drawbacks of ICT. The findings display the learners' perceptions on ICT use within the curriculum and how this relates to the available infrastructure in schools.
Keywords: Educational technology -- South Africa; Information technology -- South Africa; Education, Secondary -- Curricula -- South Africa; Computer-assisted instruction -- South Africa; Educational innovations; Information technology -- Study and teaching (Secondary) -- South Africa